Transformasi Sumber-Sumber Hukum dalam Sistem Hukum Indonesia di Era Sains dan Teknologi - Lestari, Manda Eka (Journal of Science and Technology: Alpha, 2025)
The transformation of legal sources within Indonesia's legal system has undergone significant shifts in response to advancements in science and technology. The digital era has introduced new paradigms in the formation, application, and interpretation of law, including emerging sources such as digital regulations, legal algorithms, and cyber practices. This article examines how traditional legal sources—such as statutes, customs, and jurisprudence—interact and adapt to technological innovation. Using a normative and conceptual analysis approach, the study highlights the challenges and opportunities in preserving the integrity of the national legal system amid the currents of digital globalization. The findings underscore the need for methodological and institutional renewal to ensure that Indonesia’s legal system remains relevant and responsive to contemporary developments.